Partial Purification of Antimicrobial Compounds Isolated from Mycelia of Tropical Lentinus cladopus LC4 - SUDIRMAN, LISDAR IDWAN (HAYATI Journal of Biosciences, 2010)
Lentinus cladopus LC4 produced at least eight antimicrobial compounds (ACs) which are active against plant and human pathogens. Three ACs in its crude mycelial were extracted with methanol and partial purification was carried out with silicic acid column chromatography and by thin layer chromatography (PTLC). The antimicrobial activity was tested by paper disc method and antibiographic method. The chromatography purification eluted with dichloromethane containing 5% methanol gave one active fraction (FII). This fraction which was active against X. campestris pv. glycines and showing two inhibition zones against Bacillus subtilis on bioautographic plates with the Rfs 0.8 and 0.7. FI and FIII fractions eluted with dichloromethane containing 0 and 10% methanol performed one inhibition zone with Rfs 0.8 and 0.7 respectively. However, their activities were lower than that of FII fraction. The PLTC purification gave one separate fraction with Rf value of 0.73 and it was active against X. campestris pv. glycines. The compound of Rf 0.73 fraction should be further studied using TLC and HPLC to obtain the pure substance for molecule characterization.